Cardamonin Attenuates Myocardial Ischemia/Reperfusion-Induced Ferroptosis Through Promoting STAT3 Signaling - Yang T; Wu P; Jiang L; Chen R; Jin Q; Ye G (Dove Medical Press, 2024)
Tao Yang,1,2,* Pengcui Wu,2,* Luping Jiang,2 Ran Chen,2 Qiao Jin,2 Guohong Ye2 1Department of Cardiovascular Medicine, The Second Affiliated Hospital, School of Medicine, The Chinese University of Hong Kong, Shenzhen & Longgang District People's Hospital of Shenzhen, Guangdong, 518172, People's Republic of China; 2Department of Cardiovascular Medicine, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, Changsha, 410004, People's Republic of China*These authors contributed equally to this workCorrespondence: Guohong Ye; Qiao Jin, Department of Cardiovascular Medicine, The Affiliated Changsha Central Hospital, Hengyang Medical School, University of South China, No. 161 Shaoshan South Road, Changsha, 410004, People's Republic of China, Email ygh120811@163.com; jinqiaonhdx@163.comObjective: Ferroptosis is intricately associated with the pathophysiology processes of myocardial ischemia. Cardamonin (CAR) has been shown to provide significant protection against tissue damage due to multiple ischemia/reperfusion. This study aimed to examine the cardioprotective properties of CAR in myocardial ischemia/reperfusion injury (MIRI) and provide insights into the possible mechanisms involved.Methods: An MIRI mice model was conducted by coronary artery ligation, and the effects of CAR on myocardial tissue damage were evaluated by infarct size assessment, echocardiography, and H&E staining. The extent of ferroptosis was detected by examining the levels of ferroptosis-related proteins and lipid reactive oxygen species (ROS). The function pathway of CAR was analyzed by network pharmacology and verified using Western blotting. In addition, we induced hypoxia/reoxygenation (H/R) in cardiomyocytes to detect SLC7A11 expression, ROS level, mitochondrial iron content, and oxidative stress marker levels. The target protein of CAR was identified by Western blotting and molecular docking. We then evaluated the regulatory role of STAT3 on MIRI-induced ferroptosis by silencing STAT3.Results: In our study, CAR demonstrated a reduction in myocardial histopathological damage and mitigation of ferroptosis in MIRI mice. Through network pharmacology analysis and Western blotting, our findings indicated that CAR modulates the AGE-RAGE signaling pathway, particularly impacting STAT3. Meanwhile, in vitro experiments revealed that advanced-glycation end products (AGEs) exacerbated H/R-induced ferroptosis, whereas CAR alleviated this ferroptosis in the presence of both AGEs and H/R. CAR was observed to enhance STAT3 expression in H/R+AGRs-treated cardiomyocytes. Molecular docking results demonstrated favorable binding interactions between CAR and STAT3. Our study confirmed that CAR mitigated MIRI-induced myocardial injury and ferroptosis through targeting STAT3 in mice.Conclusion: In conclusion, CAR inhibited ferroptosis by activating the STAT3 signaling, thereby mitigating MIRI.Keywords: cardamonin, myocardial ischemia/reperfusion injury, ferroptosis, STAT3, AGE-RAGE signaling pathway